Decentralization in Cambodia - Sok, Vanny; Neau, Sereth; Vanny, Marvin (Faculty of Social Science, Universitas Negeri Padang, 2025)
This study looks at the evolution of decentralization in Cambodia, mostly relating to local governance and the delivery of services. In the aftermath of the chaotic period following the Khmer Rouge regime, the Royal Government of Cambodia initiated sweeping reforms to ensure accountability and responsiveness within the local governments. A very important part of the continuous process of reforms has been the 2001 Law on Administrative Management of Commune/Sangkat, which provided a legal framework toward the empowerment of local authorities. This study, therefore, looks at key legislative frameworks, one of which is the Organic Law of 2008, and assesses the trials of political dominance, financial stranglehold from the central government, and uncertainties of the administration.